Molecular characterization of isolates of Alternariaster helianthi causing sunflower blight - M. SANTHA LAKSHMI PRASAD, J. RAJENDER*, B. PUSHPAVATHI and (Indian Phytopathology, 2016)
The genetic variability of 25 isolates of Alternaria helianthi was assessed using thirty Inter Simple Sequence Repeat (ISSR) primers. The Jaccard similarity coefficient values among A. helianthi isolates ranged from 0.22 to 1.00. The higher similarity co-efficient value of 1.00 was observed between the isolates Ah-2 and Ah-13 whereas, the least similarity co-efficient was observed between isolates Ah-10 and Ah-11 as well Ah-10 and Ah-15. At 65% similarity level, cluster analysis of similarity index data classified 25 isolates into 7 groups and the classification was presented as a dendrogram. Among the 7 groups, group-I was largest consisting of 15 isolates and was again divided into four subgroups. The isolates Ah-2 and Ah-13 showed 100 per cent genetic similarity though they were collected from two different states. The isolates Ah-5, Ah-6, Ah-10 and Ah-12 were distinctly different from other isolates forming three separate groups. Thus the present study revealed genetic relatedness between different isolates of A. helianthi. It was also found that, there was no evidence for geographical clustering of isolates with high levels of genetic similarity suggesting that the isolates are widely spread across the locations.